A fresh look at root infinitives from a cross-linguistic perspective - Kupisch, Tanja; Rinke, Esther (My University, 2008)
In this paper we examine the relation between the quantity and quality of the adult input to the child and the intensity of the root-infinitive stage in child language. We compare the languages English, French, German, Italian and Brazilian Portuguese and test whether children produce infinitives more extensively if the verb morphology of their target-languages is ambiguous with respect to the distinction between finite and nonfinite verb forms, or whether the token-frequency of nonfinite verbs in the Input is crucial. We conclude by proposing that the latter is not decisive. Rather, children seem to avoid the use of finite verb forms especially in languages whose verb paradigms are characterized by ambiguities. Root infinitives may thus be viewed as a temporary phenomenon in a phase during which children are learning the inflectional properties of their target language.
Keywords: root infinitives, finite verbs, token-frequency, optional infinitive stage, ambiguity, copula omissions, input, Brazilian Portuguese, German, Italian, French; 400